Management of recurrent haemoptysis in malignancy with combined TISSEEL and intrabronchial valves. Issue 3 (31st January 2019) - Di Michiel, James; Pan, Corinna; Ing, Alvin; Saghaie, Tajalli
Abstract : Management of recurrent haemoptysis poses a difficult clinical scenario. TISSEEL (Baxter Healthcare Corporation Deerfield, IL, USA) is a fibrin sealant often used in surgery to aid control of bleeding. However, when endoscopic TISSEEL is used independently, migration, dislodgement, or even expectoration of the fibrin clot is a common complication that may lead to recurrence of haemoptysis. Here we describe two patients with recurrent haemoptysis in the context of malignancy who underwent bronchoscopy, during which they were managed with application of topical TISSEEL to the bleeding area, followed by deployment of an intrabronchial valve, followed by a further application of TISSEEL over the valve. The combination of TISSEEL and intrabronchial valve appeared to control haemoptysis and was resistant to expectoration or migration in these two cases. Thus, this combination may provide a safe and effective therapeutic option for the control of bronchial bleeding secondary to malignancy. Abstract : It is hypothesized that intrabronchial valves would stabilize the fibrin sealant and prevent expectoration or migration. Here we describe the use of combination TISSEEL and intrabronchial valves for the management of recurrent haemoptysis secondary to malignancy. This combination therapy, to the best of our knowledge, represents a novel intervention for palliative management of this condition.